Odanacatib for the treatment of osteoporosis. (August 2015) - Boggild, Miranda K; Gajic-Veljanoski, Olga; McDonald-Blumer, Heather; Ridout, Rowena; Tile, Lianne; Josse, Robert; Cheung, Angela M
<x xml:space="preserve">Abstract</x> Introduction: Osteoporosis and fragility fractures are important public health concerns. Cathepsin K inhibitors, including <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=odanacatib&logicalOpe1=OR&field2=articletitle&text2=odanacatib&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">odanacatib, are a novel class of medications for osteoporosis whose mechanism of action is to directly inhibit bone resorption without killing osteoclasts, thereby permitting the complex coupling between bone resorption and formation to continue. Areas covered: The physiological basis for the mechanism of action of cathepsin K inhibitors is covered in addition to a review of the preclinical, Phase I, Phase II and preliminary Phase III trial data of odanacatib. Expert opinion: Evidence suggests that odanacatib has similar efficacy to bisphosphonates at increasing bone mineral density and decreasing risk of fragility fractures. Although odanacatib may preferentially inhibit bone resorption more than formation, the clinical significance of this difference in mechanism of action is not yet known. A careful analysis of the Phase III trial data is needed with specific attention to adverse events.